L'utilisation des stratégies d'apprentissage d'une langue dans un environnement des TICE - Janet Atlan (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The study of the individual differences which characterize learners is becoming more and more common in language learning research, and the use of learning strategies is an instance of individual differences which seems to be rather sensitive to the pedagogical environment. This article reports on an experimental study undertaken with students in a French technical college to determine if the use of learning strategies by a foreign language student is influenced by the technology used to present a language learning task. Oxford's Strategy Inventory for Language Learning was the principal instrument used for this study. The study showed that there was indeed some interaction between the technology used and the choice of learning strategies and the results lead to some interesting considerations on the usefulness of teaching specific learning strategies when introducing educational technology into the pedagogical environment.